Acquisition of Plate-making Process Knowledge for Smart Clothing CAD Systems (Journal of Fiber Bioengineering and Informatics, 2019)
The digital design of the clothing model currently existing in the clothing enterprise is still only an auxiliary tool in the sense of drawing. This type of garment  computer-aided design (CAD) systems can not integrate the design principles and knowledge of the clothing professional field, similar design and expert experience into the system, which leads to the need for the plate-making to rely on the personal experience of the pattern maker, and there is a problem of low design efficiency. The intelligent clothing CAD system for tailoring the needs of clothing personalization can solve the defects of traditional CAD by curing the knowledge of clothing layout design. In this paper, through the method of plate-making experiment, the knowledge of garment plate-making process is analyzed and refined, and the garment model design model is constructed by using directed graph. The method of applying the model to smart garment CAD systems is illustrated by an example.
Keywords: Intelligent Plate-making; Knowledge Acquisition; Directed Graph